Breast carcinoma metastasis to the lacrimal gland: Two case reports - NICKELSEN, MARIE N. (Oncol Lett, 2015)
A 77-year-old female, with proptosis, reduced eye motility and diplopia which had developed over two to three months and a 69-year-old female with proptosis, oedema of the eyelid, reduced motility and ptosis, which had developed over three weeks, are presented in the present study. Computed tomography scans revealed irregular lacrimal gland tumours in the two patients. The two patients had history of breast cancer. The first breast cancer metastasis in the lacrimal gland demonstrated a cribriform growth pattern containing ductal elements. The epithelial tumour cells stained positive for cytokeratin (1–8, 10, 14–16, 18 and 19), oestrogen receptor, epithelial membrane antigen (EMA), carcinoembryonic antigen (CEA) and gross cystic disease fluid protein 15 (GCDFP-15). The second metastatic tumour was positive for EMA and estrogen receptor, but variably positive for CEA and GCDFP-15. The metastasis in the lacrimal gland was a pleomorphic tumour. The tumour cells were positive for EMA and variably positive for oestrogen and CEA. Metastases to the lacrimal gland are extremely rare, and metastases to the lacrimal gland should be considered in the diagnoses of lacrimal gland tumours. The present study aimed to describe two such cases and draw attention to breast carcinomas as a differential diagnosis and the most frequent cause of lacrimal gland metastasis.